Wnt Signaling Prevents the Aβ Oligomer-Induced Mitochondrial Permeability Transition Pore Opening Preserving Mitochondrial Structure in Hippocampal Neurons. - Macarena S Arrázola; Eva Ramos-Fernández; Pedro Cisternas; Daniela Ordenes; Nibaldo C Inestrosa (PLoS ONE, 2017)
Alzheimer's disease (AD) is a neurodegenerative disorder mainly known for synaptic impairment and neuronal cell loss, affecting memory processes. Beside these damages, mitochondria have been implicated in the pathogenesis of AD through the induction of the mitochondrial permeability transition pore (mPTP). The mPTP is a non-selective pore that is formed under apoptotic conditions, disturbing mitochondrial structure and thus, neuronal viability. In AD, Aβ oligomers (Aβos) favor the opening of the pore, activating mitochondria-dependent neuronal cell death cascades. The Wnt signaling activated through the ligand Wnt3a has been described as a neuroprotective signaling pathway against amyloid-β (Aβ) peptide toxicity in AD. However, the mechanisms by which Wnt signaling prevents Aβos-induced neuronal cell death are unclear. We proposed here to study whether Wnt signaling protects neurons earlier than the late damages in the progression of the disease, through the preservation of the mitochondrial structure by the mPTP inhibition. To study specific events related to mitochondrial permeabilization we performed live-cell imaging from primary rat hippocampal neurons, and electron microscopy to analyze the mitochondrial morphology and structure. We report here that Wnt3a prevents an Aβos-induced cascade of mitochondrial events that leads to neuronal cell death. This cascade involves (a) mPTP opening, (b) mitochondrial swelling, (c) mitochondrial membrane potential loss and (d) cytochrome c release, thus leading to neuronal cell death. Furthermore, our results suggest that the activation of the Wnt signaling prevents mPTP opening by two possible mechanisms, which involve the inhibition of mitochondrial GSK-3β and/or the modulation of mitochondrial hexokinase II levels and activity. This study suggests a possible new approach for the treatment of AD from a mitochondrial perspective, and will also open new lines of study in the field of Wnt signaling in neuroprotection.